MRI assessment of the abdominal adipose tissue and the state of the abdominal aorta in patients with coronary artery disease: association with metabolic disorders - N. I. Ryumshina; O. A. Koshelskaya; I. V. Kologrivova; O. A. Kharitonova; K. A. Nasekina; V. Yu. Ussov (Бюллетень сибирской медицины)
Aim. To evaluate potential associations between quantitative features of visceral and subcutaneous adipose tissue (AT) and anthropometric characteristics of obesity, metabolic disorders, and the state of the abdominal aorta in patients with chronic coronary artery disease (CAD).Materials and methods. The study included 55 patients (average age 61.2 ± 7.2 years) with chronic CAD. Magnetic resonance imaging (MRI) was performed on a 1.5 T MRI scanner using T2-weighted spin-echo modes. The area and volume of abdominal subcutaneous (SAT) and visceral adipose tissue (VAT) were calculated at the L4–L5 level; the total volumes of abdominal SAT and VAT were determined. Parameters of lipid and carbohydrate metabolism, as well as adipokine profile were studied in the blood serum.Results. In the course of a multiple linear regression analysis, we detected the independent determinants, which described 95% of the total VAT volume variability and were represented by waist circumference (WC) and serum levels of high-density lipoprotein (HDL) cholesterol and adiponectin. The model was characterized by the significance level p < 0.000001, the residuals of the model were normal. We calculated the coefficients in the model: 1.39 for WC, –0.26 for HDL cholesterol, and –0.19 for adiponectin. We detected a positive correlation between the abdominal aorta (AA) diameter and SAT area at the L4–L5 level (rs = 0.48; p = 0.0014), which does not depend on gender, and reverse correlations between the aorta diameter and glycated hemoglobin (HbA1c) level (rs = –0.40; p = 0.0359) and postprandial glycemia (rs = –0.40; p = 0.0273). The patients with a dilated aorta (group 2), when compared with the patients with a normal aorta diameter (group 1), did not differ in the AT accumulation, but demonstrated decreased levels of HbA1c and postprandial glycemia, which resulted in a smaller number of patients with type 2 diabetes mellitus.Conclusion. We identified independent determinants of an increase in the total volume of abdominal visceral AT, such as an increase in WC and a decrease in serum adiponectin and HDL cholesterol levels. Results of the study indicate the presence of a link between the AA remodeling, accumulation of subcutaneous AT, and impaired glucose metabolism.